2009
DOI: 10.1152/ajpheart.00466.2009
|View full text |Cite
|
Sign up to set email alerts
|

Impaired function of coronary BKCachannels in metabolic syndrome

Abstract: The role of large-conductance Ca(2+)-activated K(+) (BK(Ca)) channels in regulation of coronary microvascular function is widely appreciated, but molecular and functional changes underlying the deleterious influence of metabolic syndrome (MetS) have not been determined. Male Ossabaw miniature swine consumed for 3-6 mo a normal diet (11% kcal from fat) or an excess-calorie atherogenic diet that induces MetS (45% kcal from fat, 2% cholesterol, 20% kcal from fructose). MetS significantly impaired coronary vasodil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
88
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 50 publications
11
88
0
Order By: Relevance
“…The differential consequences on the pain hypersensitivity of NS1619 with different two concentrations might be due to the differential sensitivities of neuronal and microglial BK channels. The effective dose of NS1619 in vivo was ϳ30 g (Borbouse et al, 2009). Thus, 0.072 g of NS1619 might induce microglial hyperactivation and allodynia-like behavior without affecting the neuronal excitability.…”
Section: Discussionmentioning
confidence: 99%
“…The differential consequences on the pain hypersensitivity of NS1619 with different two concentrations might be due to the differential sensitivities of neuronal and microglial BK channels. The effective dose of NS1619 in vivo was ϳ30 g (Borbouse et al, 2009). Thus, 0.072 g of NS1619 might induce microglial hyperactivation and allodynia-like behavior without affecting the neuronal excitability.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced currents and altered expression of coronary smooth muscle cell K Ca channels have been observed in animal models of LV hypertrophy, aging, and metabolic syndrome (1,3,28). K Ca channels are ubiquitously expressed in smooth muscle cells and are sensitive to both membrane potential and Ca 2ϩ influx (37,41).…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence exists indicating that profound modulation of both cardiomyocyte and smooth muscle cell electrophysiological phenotype are involved in cardiovascular disease (36, 47, 51). Calcium-activated K ϩ (K Ca ) channels play an important role in the regulation of arterial tone and vascular resistance and have been implicated in vascular dysfunction observed during the pathogenesis of left ventricular (LV) hypertrophy, hypertension, diabetes, and metabolic syndrome (3,13,28,31,41). Together, these studies suggest altered regulation of these channels may underlie impairments in coronary vascular function commonly observed in HF.…”
mentioning
confidence: 99%
“…However, few studies have examined BK Ca function in a diet-induced obesity model that reflects the etiology of primary human diet-related obesity. Furthermore, the mechanism by which BK Ca function was inhibited in these studies is unclear, with reactive oxygen species (6,20,23) or altered BK Ca subunit expression (4, 44, 45) suggested to underlie changes in vascular function. Some recent studies have suggested metabolic disease may selectively reduce vascular BK Ca ␤ 1 -subunit function, reducing the channel sensitivity to changes in membrane potential or intracellular [Ca 2ϩ ].…”
mentioning
confidence: 99%